Evolving magneto-electric device technologies. (16th June 2020) - Sharma, N; Bird, J P; Binek, Ch; Dowben, P A; Nikonov, D; Marshall, A
Abstract: Here, several classes of magneto-electric devices, and their possible implementations as complementary metal-oxide-semiconductor (CMOS) replacements, are discussed. We consider how these devices can provide considerable improvements in functionality over CMOS when employed in novel circuit architectures. In the context of the magneto-electric device technologies discussed here, we detail the expansion of benchmarking into some of the newer beyond-CMOS technologies. This has required circuit level simulations, using Cadence Spectre or Spice, and Verilog-A based models of the magneto-electric magnetic tunnel junction devices have been used for circuit validation. This has been done as part of a global effort to develop comparative benchmarking standards across logic families, even as new benchmarking methodologies are being developed, while maintaining the familiar CMOS benchmarks.